Menjual Murah Barang Dagang yang Menyelisihi Harga Pasar Menurut Tinjauan Hukum Islam (Studi Kasus di Pasar Tramo Kabupaten Maros): Selling Cheap Merchandise that Differs from Market Prices According to an Overview of Islamic Law (Case Study at Tramo Market, Maros Regency) - Ahmad Syaripudin; Muhammad Ikhsan; Mujahid Al-Islam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2024)
This research aims to find out about the causal factors and laws for selling cheap commercial goods that differ from market prices according to Islamic law (Case Study at Tramo Market, Maros Regency). The type of research used in this research is field research with a case study approach. The research results show: 1) the main factor causing cheap sales of merchandise that occurs at Tramo Maros Market is based on an agreement between sellers and buyers who are both willing, however there are several other factors that influence some traders in selling their merchandise cheaply, including; willingness, compulsion, feelings of reluctance and shame, pressure because of the need for money and goods obtained without capital; and 2) a review of Islamic law regarding the cheap sale of merchandise at Tramo Maros Market is permissible (mubah), because apart from being based on willingness, it is also in accordance with the concept of buying and selling in Islam where the conditions for determining prices are fulfilled, namely in accordance with the principles of selling. buying and selling in Islam and market mechanisms in Islam and in accordance with the concept of fair prices in Islam and the buying and selling process carried out also meets the pillars and requirements in Islam, so that this buying and selling is legal.